Effect of coagulation and filtration in slow sand filters on iron absorption in groundwater - Cahyati, Ayu; Krisman, Krisman (Universitas Riau, 2025)
The study was done to analyze the results of the filtration system of deep pearl housing groundwater using slow sand filtration methods. The analysis is based on the physical and chemical parameters of color/frequency, pH, iron and Escherichia coli with variations in coagulant, clay and alloy. The color/frequency of frequency before filtration has a value of 16.9 NTU, after value filtration declines 0.6%. The phasing of water before filtration was acid 6, having done filtration the pH of water down to 5.8 but had not reached a normal limit (6.5 – 8.5), so slow sand filters had not been effective in curbing the pH of water. The content of iron metals (Fe) before filtration was 0.1867 mg/l, after being made filtrating the content of iron metals (Fe) on the water was down to 0.021 mg/l. The content of Escherichia coli before filtration was 7 CFU / 100 ml, after exfiltration of the Escherichia coli content was reduced to zero CFU / 100 ml. The study suggests that slow sand filters use variations in coagulating and clay materials are effective in improving the quality of the groundwater in the high-yield housing projects.